Resuming elective surgical activity after the COVID-19 wave: what the patients need to know. Issue 9 (13th July 2020) - Bellini, M I; Tortorici, F; Capogni, M
Abstract: As COVID-19 outbreak enters its second phase of lockdown ease, healthcare plans involve elective surgery re-establishment to provide essential life-saving care. Patients are increasingly requesting information about their facility's readiness for safely performing surgery. This information should be open and transparent including patient's education with objective data regarding the state of the pandemic in the country and the control measures undertaken by the facility.